Beyond academics : supporting the mental, emotional, and behavioral health of students in Catholic schools - Frabutt, James M. (Emerald Publishing Limited : Information Age Publishing, 2013)
Schools must ensure that children are granted the greatest opportunity for learning possible. This means not only developing students' academic capabilities, but providing support for their emotional, behavioral, and mental health needs as well. Readers will come away with: -An increased awareness of mental, emotional, and behavioral issues and their prevalence, -A clear understanding that meeting such needs is a matter of faith, residing at the heart of what Catholic schools do: bring human life to fullness, -A knowledge base concerning what Catholic schools currently do to meet student MEB needs and a deep immersion in the perceptions of current Catholic school leaders about how to do so better, and -An appreciation that only through strategic, data informed action can schools best support the children entrusted to their care. This book foregrounds the belief that student achievement, holistic student wellness, and overall school improvement will only be attained if mental, emotional, and behavioral health in Catholic schools is advanced and supported.